2002
DOI: 10.1046/j.1365-2265.2002.01285.x
|View full text |Cite
|
Sign up to set email alerts
|

The neuro‐cardio‐endocrine response to acute subarachnoid haemorrhage

Abstract: Excessive secretion of both ANP and BNP occurs in all patients after acute subarachnoid haemorrhage and is unrelated to severity, stress hormone activation or markers of cardiac injury. Inhibition of renin-aldosterone by cardiac hormones may impair renal sodium conservation and contribute to developing hyponatraemia. In the absence of evidence for activation of natriuretic peptides within the brain, the prompt and consistent increase in both ANP and BNP strongly supports the view that the heart is the source o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 36 publications
4
60
1
3
Order By: Relevance
“…13,22,23,30) A lesion in the solitary tract nucleus also seems to alter the secretion of brain natriuretic peptide, which may also be involved in the pathogenesis of NPE. 6,7) These findings may explain why poor-grade patients with ruptured posterior circulation aneurysm were significantly more likely to sustain NPE compared with anterior circulation aneurysm, as previously reported. 25,26) The results of this study, shown in Fig.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…13,22,23,30) A lesion in the solitary tract nucleus also seems to alter the secretion of brain natriuretic peptide, which may also be involved in the pathogenesis of NPE. 6,7) These findings may explain why poor-grade patients with ruptured posterior circulation aneurysm were significantly more likely to sustain NPE compared with anterior circulation aneurysm, as previously reported. 25,26) The results of this study, shown in Fig.…”
supporting
confidence: 55%
“…12,20,21,24,31) The common pathophysiology involves massive catecholamine release, particularly norepinephrine, into the circulation immediately after aneurysm rupture, and is responsible for endothelial damage, vasoconstriction, and increased vascular permeability. 7,20,21) However, how often SAH patients complicated with NPE also have concomitant TCM (NPE-TCM) remains unclear, since evaluation of cardiac wall motion using transthorac-…”
Section: Introductionmentioning
confidence: 99%
“…In other studies with longer observation periods, hyponatremia developed frequently after SAH [1,23] and was associated with negative sodium balance [1,24] and fluid balance [25]. The authors found almost uniformly increased ANP and/or BNP concentrations and delayed activation of the renin-aldosterone axis [1,2,24]. Unfortunately, we did not measure ANP, BNP, or renin/aldosterone concentrations, and therefore cannot evaluate their potential contribution to our findings.…”
Section: Discussionmentioning
confidence: 59%
“…Serum sodium concentration and fluid balance are frequently abnormal in patients after subarachnoid hemorrhage (SAH) [1,2], with dysnatremia causing morbidity in patients with SAH [3][4][5]. Moreover, in other critically ill or emergency patient populations, both severe hyper-and hyponatremia are associated with persistent neurological deficits and high mortality [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…5,29 The presumed purpose of the stress reaction is to restore cerebral blood flow, but it can also cause adverse effects.…”
mentioning
confidence: 99%